Night watcher - Woolsoncroft, Daphne (Grand Central Publishing, 2025)
"Nola Strate is being watched, again. After an encounter with a notorious serial killer in the Pacific Northwest as a child, Nola has grown up and tried her best to forget her traumatizing night with The Hiding Man. She installed security cameras outside her Oregon home, never spoke of her experience, and now hosts Night Watch, a popular radio call-in show her semi famous father used to run. When coincidences lead Nola to believe that she is being stalked, and a caller on Night Watch has a live incident with an intruder in the caller's home, the description of whom is chillingly familiar, Nola is convinced that The Hiding Man has resurfaced and is coming for her. With a mysterious next door neighbor lurking in the shadows, more people getting hurt, the police not taking her concerns seriously, and evidence pointing towards her own father, Nola decides to become, like her listeners, a Night Watcher herself, and uncover the monster behind The Hiding Man's mask"-- Provided by publisher.